Achieving 30×30: How Different Nations Report Their Contributions to International Marine Conservation Targets - Henneker, Caitlin R; Hinchliffe, Graham; Jarvis, Rebecca M (Springer Science and Business Media LLC, 2026)
In 2022, the Convention on Biological Diversity’s Kunming-Montreal Global Biodiversity Framework was adopted. This framework includes Target 3—commonly referred to as ‘30×30’—which calls for at least 30% of land and sea to be effectively conserved and managed by 2030. Of all the nations listed on the Marine Conservation Institute’s Marine Protection Atlas (MPAtlas), 52 nations show progress towards their nations 30×30 targets through fully or highly protected Marine Protected Areas (MPAs) within 200 nautical miles of their own coastline (in their direct waters). However, six nations: the United Kingdom, United States, Australia, Argentina, France, and Aotearoa New Zealand, claim progress towards their 30×30 target through MPAs in their direct waters and in waters they claim as overseas territories, such as the waters around remote islands and other nations, further offshore (wider waters). This research raises important questions about where and why nations designate MPAs in particular locations, and what this means for equitable and effective action towards global conservation targets.